불평형 부하 운전시 3상 유도발전기 특성 해석 - 金宗謙(Jong-Gyeum Kim) (전기학회 논문지 P권, 56(3), 2007)
Hydro power supplies no pollution energy, mainly induction generator has been applied at the small capacity power station. The generating power of small hydro-electric power station connects on the 22.9kV distribution system or low voltage system in the case of three-phase four-wire supply system. There are side effects of various kinds in the 3-three phase 4-wire distribution system mixing 1-phase load and 3-phase load. This system generates the voltage unbalance by unbalanced load operating condition. They have various serious effects on generator and connection system. In this paper, we analyzed what kind of operation characteristic are happened in the induction generator by customer load variation at the 3-three phase 4-wire distribution system.